Universities as Centres of Attraction for Proactive Youth in the Ural Region - Koksharov, Viktor A.; Agarkov, Gavriil A.; Sushchenko, Anastasia D. (Economy of Regions, 2021)
Universities, comprising a strategic resource in building up a region's human capital, play a key role in ensuring sustainable economic growth. For proactive young people seeking opportunities to obtain higher education, develop professional trajectories and enhance their social connections, Russian regions lacking such facilities are seen as less attractive. This situation provokes an outflow of the most promising university candidates from the peripheral regions to the various centres of attraction. Thus, a relevant research question concerns the relationship between the quality of regional universities and the retention of young specialists, who may be expected to support the future development of industrial enterprises in the region. The assessment of interregional mobility carried out by the present study is based on an analysis of responses from applicant and graduate surveys supplemented with statistical data (Monitoring the Effectiveness of Russian Universities, Rosstat). In order to process this information, classification and data comparison methods were used. The results of the study showed that the Sverdlovsk and Tyumen oblasts are the primary centres of attraction for university entrance candidates from other Russian regions to the Urals, with the inflow of such applicants to these oblasts comprising on average 4.1 % and 13.2 %, respectively, of 18 year olds enrolling in these institutions during the 20152019 period. At the same time, the largest universities provide relevant training for the region's industrial base (up to 87 % of employed Ural Federal University graduates work in the Ural Region). The research results can be used to enhance the activities of universities and employment services in terms of developing tools for attracting and retaining proactive youth, improving the mechanisms for studying postgraduate migration in order to increase the region's attractiveness.